(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Acute cerebrovascular accidents (CVAs) remain a leading cause of morbidity and mortality worldwide. This paper reviews the modern understanding of the etiopathogenesis of CVAs, emphasizing the ischemic and hemorrhagic types. Additionally, the article explores the impact of CVAs on liver function, highlighting the multifaceted interactions between cerebral and hepatic systems. The need for interdisciplinary approaches in managing CVA patients and future research directions are also discussed.